Ascites re-compensation in HBV-related first decompensated cirrhosis after anti-viral therapy - Li, Mingyu; Zong, Zheng; Xiong, Xinmiao; Fan, Jing; Zhong, Huan; Liu, Na; Ye, Wei; Jing, Jisheng (Frontiers in Cellular and Infection Microbiology, 2023)
Effective antiviral therapy can significantly improve the long-term prognosis of HBV-related decompensated patients, and re-compensation may be achieved in part of the patients. To explore the re-compensation of ascites after HBV suppression and the risk factors, the clinical outcomes of 196 consecutive patients with HBV-related first decompensated cirrhosis of ascites treated with nucleos(t)ide analogue (NUC) were analyzed retrospectively. Among these patients, the median serum HBV DNA level was 5.0 (IQR, 3.0-6.0) log10 IU/mL before treatment. Most patients were given NUC with high barrier to resistance including ETV (152), TDF (1) and TAF (1). Initial combination of LAM plus ADV and LdT plus ADV was used in 41 patients and 1 patients, respectively. After NUC treatment, the percentage of patients with ascites regression was 77.6%, 81.4%, 70.5%, 93.8%, 80.8% at 12, 24, 36, 48, 60 months, respectively (P<0.001). The distribution of ascites severity showed that the patients’ ascites improved, with the proportion of no ascites and mild ascites gradually increased. The proportion of re-compensation of ascites defined as negative HBV DNA, improved liver function and ascites regression (off diuretics) was 59.7%, 70.0%, 52.3%, 59.4%, 46.2% at 12, 24, 36, 48, 60 months (P<0.001). The rate of ascites regression was higher in viral response (VR) cohort when compared with that in non-VR cohort. Univariate and multivariable analysis showed that level of serum ALT (OR:0.988, 95%CI, p=0.029) and load of serum HBV DNA (OR:0.78895%CI, p=0.044) at baseline were risk factors of re-compensation of ascites. This study demonstrated that antiviral therapy could reverse decompensation of ascites in HBV-related first decompensated cirrhosis and the level of ALT and HBV DNA were risk factors of ascites re-compensation.